2008
DOI: 10.1038/modpathol.2008.84
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence in situ hybridization for MDM2 gene amplification as a diagnostic tool in lipomatous neoplasms

Abstract: Well-differentiated liposarcoma/atypical lipomatous tumor and dedifferentiated liposarcoma can be difficult to distinguish from benign lipomatous neoplasms and other high-grade sarcomas, respectively. Cytogenetics in these tumors has identified ring and giant chromosomes composed of 12q13-15 amplicons including the MDM2 gene. Identifying MDM2 amplification by fluorescence in situ hybridization may prove an adjunctive tool in the diagnosis of lipomatous neoplasms. Dual color fluorescence in situ hybridization e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
181
2
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 246 publications
(194 citation statements)
references
References 21 publications
8
181
2
3
Order By: Relevance
“…[5][6][7][8][9][10]20 As a consequence, the identification of this molecular abnormality is advocated as a useful ancillary diagnostic marker, and can be considered 100% specific in the appropriate clinical and histological context. 9 Our data support the findings of others and shows that there is a good correlation between microscopic diagnosis and MDM2 amplification status.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…[5][6][7][8][9][10]20 As a consequence, the identification of this molecular abnormality is advocated as a useful ancillary diagnostic marker, and can be considered 100% specific in the appropriate clinical and histological context. 9 Our data support the findings of others and shows that there is a good correlation between microscopic diagnosis and MDM2 amplification status.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9][10]20 As a consequence, the identification of this molecular abnormality is advocated as a useful ancillary diagnostic marker, and can be considered 100% specific in the appropriate clinical and histological context. 9 Our data support the findings of others and shows that there is a good correlation between microscopic diagnosis and MDM2 amplification status. [5][6][7][8][9][10] As in the study by Zhang et al 10 we found that we had a tendency to 'overcall' lipomas, whereas the risk of 'under-calling' an atypical lipomatous tumor (MDM2 amplification-positive) was much less.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations